Spinal Cord Stimulation as an Alternative to Opioid for Axial Neck and Back Pain: A Case Series - Mullins, Graeme Sampson; Burns, Joanna Jane; Schneider, Andre Perillier; El Helou, Antonios (Frontiers in Pain Research, 2022)
Introduction: Spinal cord stimulation is emerging as a minimally invasive technique for the treatment of persistent spinal pain syndrome (PSPS). Methods: We describe a case series of 25 individuals with PSPS who underwent implantation of a spinal cord stimulator device between 2017 and 2021. Results: There was a significant reduction in the mean visual analogue scale pain scores in the immediate post-operative phase 8.61 vs. 2.30, p < 0.001). There were twelve patients with pre-operative opioid consumption and 75% showed reduction of use with a significantly lower average daily dose (66.8 vs. 26.9 meq/D, p < 0.05). There was a significant reduction in the Oswestry disability index at post-operative follow-up visits (p<0.001). There were no major perioperative or long-term complications from the procedure in follow-up. Conclusion: Analysis of this cohort suggests successful long-term treatment of a diverse set of patients with PSPS with SCS with meaningful improvement in quality of life and reduction in opioid consumption.